2020
DOI: 10.1097/yct.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Electroconvulsive Therapy in Children and Adolescents in the Czech Republic

Abstract: Objectives:The aim of this study was to describe the practice of electroconvulsive therapy (ECT) in child and adolescent patients in the Czech Republic. Methods:We conducted a mail questionnaire survey among Czech facilities associated with the Association of Child and Adolescent Psychiatry, and university hospitals with inpatient psychiatric wards, focused on the practice of ECT between 2013 and 2017 in patients younger than 18 years.Results: Of 18 approached facilities, 13 had access to ECT, and only 6 used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is important to state here that there were real-life incidents of ECT malpractice, some not that far in the past, such as the scandalous usage of ECT in a group of young students allegedly suffering from "video games addiction" in China (14). It is important to note that nowadays, ECT is applied under a brief general anesthesia in developed countries, has specific indications (pharmaco-resistant affective and psychotic disorders) and in principle requires consent from the patient (16)(17)(18)(19). The application of ECT without the patient's consent is not common and constitutes life-threating conditions, such as syndrome of catatonia or severe psychotic illnesses with malnourishment (20).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to state here that there were real-life incidents of ECT malpractice, some not that far in the past, such as the scandalous usage of ECT in a group of young students allegedly suffering from "video games addiction" in China (14). It is important to note that nowadays, ECT is applied under a brief general anesthesia in developed countries, has specific indications (pharmaco-resistant affective and psychotic disorders) and in principle requires consent from the patient (16)(17)(18)(19). The application of ECT without the patient's consent is not common and constitutes life-threating conditions, such as syndrome of catatonia or severe psychotic illnesses with malnourishment (20).…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature research yielded only 24 articles on ECT in child and adolescent psychiatry-aside from individual case reports (Table 1). 12,14,22,30 Altogether, 1096 cases were published internationally. No metaanalyses or randomized controlled studies were found.…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…For its use on adolescents, it had been supported by the American Academy of Child and Adolescent Psychiatry (AACAP) since 2004 [ 12 ]. However, due to restrictions on research on adolescents and legal limitations [ 13 , 14 ], few large studies of ECT on adolescents are available, nonetheless, many studies still demonstrated that ECT could be considered amongst MDD adolescents accompanied by SI/SA [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%